Large scale validation and refinement of integrated pest management strategy for basmati rice (Oryza sativa) in farmers’ participatory mode - KUMAR, ANOOP; KHOKHAR, MUKESH KUMAR; CHANDER, SUBHASH; SINGH, S P; PARVEZ, RASHID; DABAS, J P S; KUMAR, RAKESH; CHOUDHARY , MANOJ; SINGH, S K (The Indian Journal of Agricultural Sciences, 2025)
Rice (Oryza sativa L.) is an economically important food crop and its yield is severely affected by insect-pests and diseases. The study was carried out during rainy (kharif) season of 2020 to 2023 at village Nidana, Rohtak, Haryana to manage pest problems with minimum use of pesticides, in basmati rice cv. PB1718 under farmers’ participatory mode using integrated pest management (IPM). The results revealed that IPM proved effective in significantly reducing yellow stem borer incidence (21.91%), brown plant hopper (45.95%), bakane disease (86.02%), bacterial leaf blight (78.92%) and blast (55.30%), along with an increase in natural enemy population i.e. spiders compared to farmer practice (FP). The population of spiders was higher in IPM (1.07/hill) compared to FP (0.22/hill). IPM practice has advantage in reducing the cost of cultivation (15.60%) by decreasing number of pesticides application (48.72%) as well as amount of pesticides’ active ingredient (82.29%). The total grain yield under IPM increased by 8.48% over FP because of reduced pest incidence and adoption of good agriculture practices. The benefit-cost ratio in IPM (2.80) was superior to FP (2.17) with 29.51% higher net return. The refined IPM strategies proved economically viable, provided an effective pest suppression in an eco-friendly manner by conserving natural enemies through minimisation of pesticide applications, and thus adoptable under farmers’ field conditions.